INTERPRETATION OF THE 3D GEOELECTRICAL MODEL OF THE INTERSECTION AREA OF THE ZVIZDAL-ZALISKA AND NEMYRIVSK FAULT ZONES - Ilienko, V.; Burakhovich Т.; Kushnir А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The interpretation of the deep three-dimensional geoelectricalal model of the central part of the Zvizdal-Zaliska and Brusyliv fault zones of the Ukrainian shield, which was built with the involvement of data from experimental observations of the Earth’s low-frequency electromagnetic field conducted in 2019 by the Institute of Geophysics named after S.I. Subotin of the National Academy of Sciences of Ukraine, within the Ordyntsi-Lobachiv and Zoziv-Stryzhavka profiles was done. Experimental materials were processed with the PRC_MTMV software package, tipper estimates were obtained for periods of geomagnetic variations from 50 to 3400 s and curves of apparent resistivity (amplitude values and impedance phases) from 10 to 10000 s. Based on the qualitative analysis of magnetovariational profiling parameters, magnetotelluric sounding curves and pseudo-sections, several local near-surface structures of complex orientation in space were identified, which are confined to the Pogrebyshchensky and Ogiivskyi faults, areas of separate parts of the Zvizdal-Zaliska, Brusyliv and Nemyriv fault zones, as well as their convergence , and outside the fault zones in the crystalline massive of the Ukrainian shield.The main result of the geological-geoelectrical interpretation of the 3D model is the discovery of new anomalies of low resistivity in the near-surface part of the earth’s crust (from the surface to 0.5-2 km), which correspond to the structural and metallogenic features of the study area; confirmation and detailing of the anomalously heterogeneous distribution of resistivity in the tops of the upper mantle at depths from 70 to 120 km west of the Ukrainian shield. The area of intersection of the Zvizdal-Zaliska and Nemyrivs fault zones is characterized by both a galvanically connected spatially diverse system and local separate near-surface anomalies with low resistivity from 5 to 100 Ohm·m, most of which dip to 0.5-1 km.It is shown that there are connections between conductivity and structural features of the Zvizdal-Zaliska, Brusyliv and Nemyriv fault zones. In addition, some anomalies are found in the granite migmatites of the Ros’ structural-formation zone, outside the tectono-metasomatic mineragenic zones. As a rule, anomalies are confined to zones of disintegration of crystalline basement rocks, elongated zones of metasomatization, and areas of distribution of graphitized rocks; moreover, some of the surface anomalies correspond to regions of weathering crusts. The conducted geological-geoelectrical analysis of the model showed that several areas require further study, namely the sub-latitude anomaly west of the Zoziv-Stryzhavka profile and the complex-shaped anomaly in the eastern part of the study area. As promising for the search for minerals, which meets the geoelectrical criteria, the area of the anomaly within the Brusyliv fault zone with a depth of up to 2 km is highlighted.